Methyl paraben detection in cosmetic products by synthesis of azo compounds using infrared spectroscopy - ALCHAB, Faten Ali (Latakia University Journal -Medical Sciences Series, 2019)
الكشف عن الميثيل بارابين في مستحضرات التجميل عن طريق اصطناع مركبات الآزو باستخدام مطيافية الأشعة تحت الحمراء A new method for the detection of methylparaben which is often used as preservative, alone or in combination with other parabens using infrared spectroscopy was developed. A good method for detection of methylparaben was developed using the oxidation reactions between methylparaben and many aromatic amines in order to form the colorful azo dye compounds. There have been numerous attempts to select the ideal conditions for completion of diazotization and coupling reactions of and put in terms of determining the quantities of reactants and determining the appropriate temperature to complete the interaction. The complexes were then studied and identified using infrared spectra. The proposed method was successfully applied to the assay of methylparaben in cosmetic products. تم تطوير طريقة جديدة للكشف عن الميثيل بارابين المستخدم كمادة حافظة ، بمفرده أو بالاقتران مع البارابينات الأخرى و ذلك باستخدام مطيافية الأشعة تحت الحمراء. اعتمدت هذه الطريقة على إنجاز تفاعلات الأكسدة بين الميثيل بارابين والعديد من الأمينات العطرية بهدف تشكيل مركبات الآزو الملونة. و قد تعددت المحاولات بهدف اختيار الشروط المثالية لإتمام تفاعلات الديئزة و التزاوج من حيث تحديد كميات المواد المتفاعلة وتحديد درجة الحرارة المناسبة لإتمام التفاعل و من ثم تم دراسة المركبات المتشكلة، و تحديد هويتها باستخدام مطيافية الأشعة تحت الحمراء. تم تطبيق الطريقة المقترحة بنجاح للكشف عن الميثيل بارابين في مستحضرات التجميل.